THE ROLE OF ISLAMIC BOARDING SCHOOL TRADITIONS IN STUDENT DEVELOPMENT IN FUTURE LIFE - Abuddar, Abuddar; Zubaidi, Ahmad; Maulana, Zaki (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic boarding schools, known as pesantren, play a crucial role as Islamic educational institutions in shaping students' character, knowledge, and skills to face future challenges. These institutions have a long-standing tradition rich in Islamic values, discipline, and independence, which are deeply embedded in their daily practices. Pesantren not only focuses on providing religious education but also emphasizes moral, social, and life skills relevant to contemporary needs. The holistic approach of pesantren nurtures students' spiritual, intellectual, and social development, fostering a balance between academic knowledge and moral integrity. Furthermore, the pesantren environment encourages strong discipline and self-reliance, shaping students to become resilient and adaptable individuals. This article explores the unique traditions of Islamic boarding schools and their influence on students' development, analyzing the implications for their future roles in society as leaders, professionals, and morally responsible citizens who contribute positively to their communities and beyond.